Health Service Use and Quality of Life Recovery 12 Months Following Major Osteoporotic Fracture: Latent Class Analyses of the International Costs and Utilities Related to Osteoporotic Fractures Study (ICUROS). (14th October 2020) - Talevski, Jason; Sanders, Kerrie M; Busija, Ljoudmila; Beauchamp, Alison; Duque, Gustavo; Borgström, Fredrik; Kanis, John A; Svedbom, Axel; Connaughton, Catherine; Stuart, Amanda L; Brennan‐Olsen, Sharon L
Abstract: Major osteoporotic fractures (MOFs) are associated with a rapid decline in health‐related quality of life (HRQoL); however, there is limited knowledge about which healthcare services positively affect HRQoL postfracture. This study aimed to identify specific combinations of health service use associated with recovery of HRQoL 12 months post‐MOF. The analyses included 4126 adults aged ≥50 years with an MOF (1657 hip, 1354 distal forearm, 681 vertebrae, 434 humerus) participating in the International Costs and Utilities Related to Osteoporotic fractures Study (ICUROS), a multinational observational study (Australia, Austria, Estonia, France, Italy, Lithuania, Mexico, Russia, Spain, United Kingdom, and United States). HRQoL at prefracture and 12 months postfracture was measured using the EuroQoL questionnaire (EQ‐5D‐3L). Health service use data were collected via participant interviews and medical record reviews including in‐hospital care; outpatient care; community services; and medication use. Data analyses involved two stages: (i) latent class analyses to identify different combinations of health service use ("classes"); and (ii) logistic regression to assess effects of classes on HRQoL recovery. Analyses were repeated excluding hip fractures (non‐hip MOFs). Overall, 2057 MOF participants (49.9%) recovered to their prefracture HRQoL at 12‐month follow‐up; this proportion was higher for non‐hip MOFs ( n = 1439; 58.3%). Several distinct classes were identified across countries (range, 2–5 classes). Classes that were associated with increased odds of HRQoL recovery were characterized by a combination of hospital presentations without admission; outpatient department visits; allied health visits; vitamin D/calcium supplementation; and/or non‐opioid analgesic use. Similar classes were observed for non‐hip MOFs. Understanding country‐specific healthcare service pathways that influence greater recovery of HRQoL, particularly services that are uncommon in some countries and routine in others, could improve postfracture care on a global scale. © 2020 American Society for Bone and Mineral Research (ASBMR).